Spatial Mapping of Landslide Susceptibility Level in Pacitan District Using Analytical Hierarchy Process and Natural Break - Fariza, Arna; Basofi, Arif; Hamida, Silfiana Nur (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2022)
Pacitan district has a high potential for landslides. Landslide is a hydrometeorological disaster that causes loss of life, property loss, and environmental damage. Disaster preparedness is very necessary for the wider community in dealing with landslide emergency response situations. Applications to determine the level of vulnerability to landslides are very useful to minimize the impact and losses on the Pacitan community. This study aims to make an application for assessing the level of landslide susceptibility using the analytical hierarchy process and natural break based on the factors that cause landslides in the sub-district or village of Pacitan district. The factors that cause landslides in Pacitan district consist of weather, history of landslides, land slope, and history of earthquakes. The results of the AHP and natural break classifications are visualized in the form of a spatial map into 3 categories, namely high, medium and low vulnerability levels. The results of the AHP classification and natural break in the 2016-2020 data have a good average GVF value of 0.77. This shows that in general, the results of the 2016-2020 data classification are correct. Mobile device-based applications provide convenience for the public in accessing information as an effort to improve landslide disaster preparedness.